Caracterización estructural, histológica y espectral del cultivo de papa (solanum tuberosum) en el barrio Culacusig, cantón Sigchos, provincia de Cotopaxi. 2014 - Suárez Vaca, Narcisa Nataly (2015)
A research study on “Structural, Histological, and Spectral Characterization of potato (Solanum tuberosum)”, was carried out in Culacusig Neighborhood, Sigchos Town, Cotopaxi Province. The general purpose of this study was to generate, systematize, and standardize the graphic and spectral information on digital media of the macro and micro structures of potato, for academic and research applications. The study was conducted using high resolution images captured with high-tech equipment. It allowed for identification of each part of the plant, followed with didactic theoretical information. An interactive website that is user-friendly was designed. Three fundamental aspects were taken into account. Firstly, a structural characterization using a 46-megapixel SIGMA camera with 3 RGB sensors and a 250mm zoom lens visualized macro structural images. It showed the basic characteristics of the plant (roots, tuber, steam, leaves, flowers, fruit, and seed). Meanwhile, a stereoscope visualized macro structural images (seeds, sepal, petal, etc). Secondly, a histological characterization was created using an AMSCOPE microscope, 10x, 20x, 80x lenses, and microscopy equipment to generate microstructural images (conducting vessels, tissues, epidermis, stomata, etc)….